Implementation of DC Motor Driver in Autoclave Reactor in Nickel Laterite Ore Processing - Afandy, Moh .; Rianto, Muhammad Ikbal; Mubarak, Abdul Haris (Jambura Journal of Electrical and Electronics Engineering, 2025)
This study aims to design and test a DC motor speed monitoring system in the process of stirring acid solution and Nickel Laterite ore in an Autoclave reactor tube. The control system uses a PWM (Pulse Width Modulation) signal with a constant duty cycle of 100% which is given to the MOSFET-based H-Bridge topology DC motor driver circuit. The determination of the duty cycle is based on the RPM rotation of the stirrer in the reactor tank with a multilevel test from 10% - 100%. Testing was carried out in two processing conditions, each with an acid concentration of 4% and 5%, to evaluate system performance against variations in viscosity load. The results of the study showed that the system was able to maintain the stability of the motor rotation speed in the nickel processing range with a leach solution content of 4% and 5% with an average speed of 193 RPM, even though there was an increase in load due to the concentration of the solution. The performance of the driver circuit proved effective in distributing power continuously without symptoms of overheating or switching interference, and was able to protect the system from the effects of reverse voltage. The mixing process showed homogeneous results with adequate stirring efficiency in both solution conditions. The final result in the form of filtrate liquid and residual residue is obtained from the process evaluation. The monitoring system and DC motor driver designed have shown reliable performance in laboratory-scale reactor stirring applications with a local monitor system, and have the potential to be further developed into an adaptive control system based on feedback sensors for energy efficiency and a remote monitoring and control system.Penelitian ini bertujuan untuk merancang serta menguji sistem monitoring kecepatan motor DC pada proses pengadukan larutan asam dan Nikel Laterite ore dalam tabung reaktor Autoclave. Sistem kontrol menggunakan sinyal PWM (Pulse Width Modulation) dengan dutycycle konstan sebesar 100% yang diberikan pada rangkaian driver motor DC  topologi H-Bridge berbasis MOSFET. Penentuan dutycycle didasarkan pada putaran RPM pengaduk pada tangka reactor dengan pengujian bertingkat dari 10 % - 100%. Pengujian dilakukan dalam dua kondisi proses pengolahan, masing-masing dengan konsentrasi asam 4% dan 5%, untuk mengevaluasi performa sistem terhadap variasi beban viskositas. Dari hasil penelitian menunjukkan bahwa sistem mampu mempertahankan kestabilan kecepatan putar motor dalam rentang pemprosesan nikel dengan kadar larutan pelindi 4% dan 5% dengan kecepatan rata-rata 193 RPM, meskipun terdapat peningkatan beban akibat konsentrasi larutan. Kinerja rangkaian driver terbukti efektif dalam mendistribusikan daya secara kontinu tanpa gejala overheat atau gangguan switching, serta mampu melindungi sistem dari efek tegangan balik. Proses pencampuran menunjukkan hasil homogen dengan efisiensi pengadukan yang memadai pada kedua kondisi larutan. Hasil akhir berupa cairan filtrate dan sisa residu diperoleh dari valuasi proses. Sistem monitoring dan driver motor DC yang dirancang telah menunjukkan performa andal dalam aplikasi pengadukan reaktor skala laboratorium dengan system local monitor, serta berpotensi dikembangkan lebih lanjut menuju sistem kontrol adaptif berbasis sensor umpan balik untuk efisiensi energi dan system monitoring dan control jarak jauh.